2012
DOI: 10.2119/molmed.2012.00033
|View full text |Cite
|
Sign up to set email alerts
|

R-roscovitine Reduces Lung Inflammation Induced by Lipoteichoic Acid and Streptococcus pneumoniae

Abstract: Bacterial pneumonia remains associated with high morbidity and mortality. The gram-positive pathogen Streptococcus pneumoniae is the most common cause of community-acquired pneumonia. Lipoteichoic acid (LTA) is an important proinflammatory component of the gram-positive bacterial cell wall. R-roscovitine, a purine analog, is a potent cyclin-dependent kinase (CDK)-1, -2, -5 and -7 inhibitor that has the ability to inhibit the cell cycle and to induce polymorphonuclear cell (PMN) apoptosis. We sought to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 47 publications
(69 reference statements)
3
37
0
Order By: Relevance
“…Lungs, blood, spleens, and livers were harvested 6, 24, or 48 h postinfection for quantitative bacterial cultures as described (n = 8 or 16 per group at each time point) [23,24]. Neutrophil counts in bronchoalveolar lavage (BAL) fluid were determined as described [25]. In separate studies, mice were followed for 4 days and survival was monitored at least every 12 h (n = 20 per group).…”
Section: Methodsmentioning
confidence: 99%
“…Lungs, blood, spleens, and livers were harvested 6, 24, or 48 h postinfection for quantitative bacterial cultures as described (n = 8 or 16 per group at each time point) [23,24]. Neutrophil counts in bronchoalveolar lavage (BAL) fluid were determined as described [25]. In separate studies, mice were followed for 4 days and survival was monitored at least every 12 h (n = 20 per group).…”
Section: Methodsmentioning
confidence: 99%
“…Seliciclib was also effective in a Str. pneumoniae pneumonia model [204]. However, it has cytostatic properties and is being studied for small cell lung cancer, lymphomas and other malignancies [205].…”
Section: Strategies To Accelerate the Resolution Of Inflammationmentioning
confidence: 99%
“…However, it has cytostatic properties and is being studied for small cell lung cancer, lymphomas and other malignancies [205]. Whether it is suitable for immunomodulation in bacterial infections will depend on the severity of the immune defect induced by this compound [204].…”
Section: Strategies To Accelerate the Resolution Of Inflammationmentioning
confidence: 99%
“…Several mouse models of lung inflammation or injury were efficiently treated with roscovitine by intraperitoneal administration: bleomycin-induced lung injury [74], lipoteichoic acid and Streptococcus pneumonia -induced lung inflammation [75], mechanical ventilation -induced lung injury [76]. Furthermore, roscovitine has been evaluated in phase IIa clinical trials against NSC lung cancer, where a substantial increase in overall survival was observed (388 versus 218 days in the placebo arm), despite no difference in progression free survival [68].…”
Section: Roscovitine a Wide Potential Kinase Inhibitormentioning
confidence: 99%
“…Inhibition of the NFκB pathway by CR8, an analogue of roscovitine, was also observed in chronic lymphocytic leukemia cells [158]. The anti-inflammatory effect of roscovitine via enhanced apoptosis of neutrophils was confirmed in a zebrafish inflammatory model [159, 160], a mouse model with pulmonary inflammation induced by Streptococcus pneumoniae and lipoteichoic acid (a pro-inflammatory constituent of gram positive bacteria) [75], a mouse model of ventilator-induced lung injury [76] and an experimental mouse model of pneumococcal meningitis [161]. It was also shown that roscovitine, by inhibiting CDK2 and CDK5, blocks endothelial activation and leucocyte/endothelial cell interactions, contributing to the anti-inflammatory effect [162].…”
Section: Roscovitine and Cystic Fibrosismentioning
confidence: 99%